Light-emitting device, preparation method thereof and display device

By introducing high refractive index materials into the electron transport layer of the light emitting device, the problem of large light energy loss in QLED is solved, and a higher light extraction rate and lower preparation cost is achieved.

CN119451398APending Publication Date: 2025-02-14TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310963162.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

现有量子点发光二极管(QLED)因不同功能层之间的折射率差异,导致光能损耗较大,且现有降低光能损耗的方法需增加复杂的工序,导致制备成本上升和效率下降。

Method used

A high refractive index material is introduced into the electron transport layer of the light emitting device with a refractive index greater than 1.5, forming a large scattering center to reduce the waveguide loss of light.

Benefits of technology

Effectively reduce the light energy loss in the light emitting device, improve the light extraction rate, reduce the preparation cost, and improve the preparation efficiency and yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451398A_ABST
    Figure CN119451398A_ABST
Patent Text Reader

Abstract

The invention provides a light-emitting device and a preparation method thereof, and a display device.The light-emitting device comprises an anode and a cathode which are oppositely arranged, a light-emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the cathode and the light-emitting layer, materials of the electron transport layer comprise an N-type semiconductor material and a high-refractive-index material, and the refractive index of the high-refractive-index material is larger than 1.5. According to the light-emitting device, the high-refractive-index material with the high refractive index is added into the electron transmission layer, the high-refractive-index material forms a large number of scattering centers, light bound in the light-emitting device is scattered out, the waveguide loss of the light in the light-emitting device can be effectively reduced, and therefore the light extraction efficiency can be improved, and the light energy loss can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a light-emitting device and a method for preparing the same, and a display device. Background Art

[0002] Quantum dots are a type of semiconductor clusters with a size of 1 to 10 nm. Due to the quantum size effect, they have optoelectronic properties with adjustable band gaps. By regulating the size of quantum dots, the required specific wavelength of light emission can be achieved. They can be used in light-emitting diodes, solar cells, bioluminescent markers and other fields. Quantum dots can be divided into group II-VI quantum dots (such as CdSe, CdS, CdTe, ZnSe, ZnS, etc.), group III-V quantum dots (such as GaAs, InAs, InP, etc.), carbon quantum dots or silicon quantum dots. Currently, CdSe QDs are the most studied, and their emission wavelength tuning range can range from blue light to red light.

[0003] In traditional inorganic electroluminescent devices, electrons and holes are injected from the cathode and anode respectively, and then recombine in the light-emitting layer to form excitons to emit light. The conduction band electrons in wide-bandgap semiconductors can be accelerated under high electric fields to obtain high enough energy to collide with QDs to make them emit light. As a new type of inorganic semiconductor fluorescent material, semiconductor quantum dot materials have important commercial application value.

[0004] However, quantum dot light-emitting diodes (QLEDs) formed by stacking multiple functional layer materials are prone to light energy loss due to the large difference in refractive index between different functional layers. Although there are many methods that can be used to reduce the light energy loss of QLED devices, such as adding lenses to the outside of QLED devices, or using photolithography, nanoimprinting and other technologies to form grating structures, these methods all require the addition of more complicated processes, which leads to an increase in preparation costs and a decrease in preparation efficiency and yield. Summary of the invention

[0005] Embodiments of the present application provide a light-emitting device and a method for manufacturing the same, and a display device.

[0006] The technical solution of this application is as follows:

[0007] In a first aspect, the present application proposes a light-emitting device, comprising an anode and a cathode arranged opposite to each other, a light-emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the cathode and the light-emitting layer, characterized in that the material of the electron transport layer comprises an N-type semiconductor material and a high refractive index material, wherein the refractive index of the high refractive index material is greater than 1.5.

[0008] Optionally, in some embodiments of the present application, the material of the electron transport layer includes the N-type semiconductor material and the high refractive index material dispersed between the N-type semiconductor materials.

[0009] Optionally, in some embodiments of the present application, the high refractive index material is disposed on a side of the electron transport layer close to the light-emitting layer.

[0010] Optionally, in some embodiments of the present application, the molar ratio of the N-type semiconductor material to the high refractive index material is 1:0.001 to 1:0.05.

[0011] Optionally, in some embodiments of the present application, the average particle size of the high refractive index material is 15-25 nm; and / or

[0012] The average particle size of the N-type semiconductor material is 5-12 nm.

[0013] Optionally, in some embodiments of the present application, the high refractive index material is selected from one of a polymer compound or a first compound, wherein the polymer compound is selected from at least one of poly(pentabromophenyl methacrylate), poly(pentabromobenzyl acrylate), poly(pentabromobenzyl methacrylate), poly(2,4,6-tribromophenyl methacrylate), poly(vinyl phenyl sulfate), poly(2-vinylthiophene), and poly(2-chlorostyrene) or a block copolymer of more than one polymer monomer; the first compound includes one or more of a titanium compound, a zirconium compound, a niobium compound, a tantalum compound, and a hafnium compound, the titanium compound includes titanium dioxide, the zirconium compound includes zirconium oxide, the niobium compound includes niobium oxide, the tantalum compound includes tantalum oxide, and the hafnium compound includes hafnium oxide; and / or

[0014] The N-type semiconductor material is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, and the doping ratio is 0-50%; the II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.

[0015] Optionally, in some embodiments of the present application, the cathode and the anode are selected from doped metal oxide particle electrodes, composite electrodes of metal and metal oxide, graphene electrodes, carbon nanotube electrodes, metal electrodes or alloy electrodes, the material of the doped metal oxide particle electrodes is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or

[0016] The material of the light-emitting layer is an organic light-emitting material or a quantum dot light-emitting material, and the organic light-emitting material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermal One or more of an activation delay material, a polymer containing BN covalent bonding, a hybrid localized charge transfer excited state material, and an exciplex luminescent material, wherein the quantum dot luminescent material is selected from one or more of a single structure quantum dot, a core-shell structure quantum dot, and a perovskite semiconductor material, wherein the material of the single structure quantum dot, the core material of the core-shell structure quantum dot, and the shell material of the core-shell structure quantum dot are selected from at least one of a II-VI group compound, an IV-VI group compound, a III-V group compound, and an I-III-VI group compound, respectively, wherein the II-V Group I compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSe S, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZ At least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe,The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2, the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors, and the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs, + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the organic-inorganic hybrid perovskite semiconductors, the general structural formula of which is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0017] Optionally, in some embodiments of the present application, the light-emitting device further comprises a hole functional layer disposed between the anode and the light-emitting layer, and the hole functional layer comprises a hole injection layer and a hole transport layer;

[0018] The material of the hole transport layer is selected from 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-di(4-(N,N'-diphenyl-amino)-N,N'-bis(phenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-di(4-(N,N'-diphenyl-amino)-N,N'-bis(phenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-di ... triphenylamine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine) (poly-TPD), polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly [2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or

[0019] The material of the hole injection layer is selected from at least one of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0020] In a second aspect, the present application further proposes a method for preparing a light-emitting device, comprising:

[0021] providing a substrate having an anode;

[0022] forming a light-emitting layer on the anode;

[0023] forming an electron transport layer on the light-emitting layer;

[0024] forming a cathode on the electron transport layer; or

[0025] providing a substrate having a cathode;

[0026] forming an electron transport layer on the cathode;

[0027] forming a light-emitting layer on the electron transport layer;

[0028] forming an anode on the light-emitting layer;

[0029] The material of the electron transport layer includes an N-type semiconductor material and a high refractive index material, and the refractive index of the high refractive index material is greater than 1.5.

[0030] Optionally, in some embodiments of the present application, the step of forming an electron transport layer on the light-emitting layer includes:

[0031] Providing a mixed solution containing the N-type semiconductor material and the high refractive index material;

[0032] Forming the electron transport layer on the light-emitting layer by using the mixed solution; or

[0033] Providing a first solution containing the high refractive index material and a second solution containing the N-type semiconductor material;

[0034] forming a first film layer on the light-emitting layer using the first solution, and then forming a second film layer on the first film layer using the second solution;

[0035] Wherein, the first film layer and the second film layer constitute the electron transport layer.

[0036] Optionally, in some embodiments of the present application, the step of forming an electron transport layer on the cathode includes:

[0037] Providing a mixed solution containing the N-type semiconductor material and the high refractive index material;

[0038] Forming the electron transport layer on the light-emitting layer by using the mixed solution; or

[0039] Providing a third solution containing the N-type semiconductor material and a fourth solution containing the high refractive index material;

[0040] forming a third film layer on the cathode by using the third solution, and then forming a fourth film layer on the fourth film layer by using the fourth solution;

[0041] Wherein, the third film layer and the fourth film layer constitute the electron transport layer.

[0042] Optionally, in some embodiments of the present application, the molar ratio of the N-type semiconductor material to the high refractive index material in the electron transport layer is 1:0.001 to 1:0.05; and / or

[0043] The average particle size of the high refractive index material is 15-25 nm; and / or

[0044] The average particle size of the N-type semiconductor material is 5-12 nm.

[0045] Optionally, in some embodiments of the present application, the high refractive index material is selected from one of a polymer compound or a metal oxide, wherein the polymer compound is selected from at least one of poly(pentabromophenyl methacrylate), poly(pentabromobenzyl acrylate), poly(pentabromobenzyl methacrylate), poly(2,4,6-tribromophenyl methacrylate), poly(vinyl phenyl sulfate), poly(2-vinylthiophene), and poly(2-chlorostyrene); the metal oxide is selected from zirconium oxide; and / or

[0046] The N-type semiconductor material is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, the II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.

[0047] In a third aspect, the present application further proposes a display device, comprising the light-emitting device, or a light-emitting device prepared by the method for preparing the light-emitting device.

[0048] The technical solution of the present application is to add a high-refractive-index material with a high refractive index to the electron transport layer. The high-refractive-index material forms a large number of scattering centers, which scatter the light bound in the light-emitting device, thereby effectively reducing the waveguide loss of the light in the light-emitting device, thereby improving the technical problem of large light energy loss in the existing light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0050] Figure 1 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;

[0051] Figure 2 is another structural schematic diagram of the light-emitting device provided in an embodiment of the present application;

[0052] Figure 3 It is a schematic diagram of a process for preparing a positive light-emitting device provided in an embodiment of the present application;

[0053] Figure 4 It is a schematic flow chart of a method for preparing an inverted light-emitting device provided in an embodiment of the present application.

[0054] Description of the drawings: 1- anode, 2- cathode, 3- light-emitting layer, 4- electron transport layer, 5- hole injection layer, 6- hole transport layer. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0056] In the present application, "and / or" describes the association relationship of associated objects, indicating that there are three types of relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural.

[0057] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b and c can be single or multiple, respectively.

[0058] In the present application, when another layer is formed "on" a certain layer, the so-called "on" is a broad concept, which may mean that the formed another layer is adjacent to the certain layer, or may mean that there are other spacing structural layers between the another layer and the certain layer. For example, when a top electrode is formed "on" the first carrier functional layer, the so-called "on" may mean that there are other spacing structural layers between the formed top electrode and the first carrier functional layer, such as a light-emitting layer.

[0059] In order to solve the technical problem of large light energy loss of existing light emitting devices, this embodiment proposes a light emitting device, such as Figure 1 As shown, it includes an anode 1 and a cathode 2 arranged opposite to each other, a light-emitting layer 3 arranged between the anode 1 and the cathode 2, and an electron transport layer 4 arranged between the cathode 2 and the light-emitting layer 3, and the material of the electron transport layer 4 includes an N-type semiconductor material and a high refractive index material, wherein the refractive index of the high refractive index material is greater than 1.5.

[0060] In this embodiment, by adding the high refractive index material with a high refractive index into the electron transport layer, the high refractive index material forms a large number of scattering centers, which scatter the light bound in the light-emitting device, and can effectively reduce the waveguide loss of the light in the light-emitting device, thereby improving the technical problem of large light energy loss in the existing light-emitting device.

[0061] Furthermore, in this embodiment, the higher the refractive index of the high refractive index material, the more the light converges toward the light emitting position of the light emitting device, thereby increasing the light extraction rate of the light emitting device and reducing the light energy loss. In this embodiment, the refractive index of the high refractive index material is greater than 1.5. If the refractive index of the high refractive index material is less than 1.5, the improvement in the light extraction efficiency of the light emitting device is not obvious, and it is difficult to effectively improve the technical problem of large light energy loss of the light emitting device.

[0062] In one embodiment, the material of the electron transport layer includes the N-type semiconductor material and the high refractive index material dispersed between the N-type semiconductor materials. In this embodiment, without affecting the electrical properties of the electron transport layer, the high refractive index material dispersed between the N-type semiconductor materials forms a large number of scattering centers, so that the light emitted by the light-emitting layer is more concentratedly scattered or transmitted to the light-emitting position at the top or bottom of the light-emitting device, which can effectively increase the light extraction efficiency of the light-emitting device and reduce light energy loss.

[0063] In one embodiment, the high refractive index material is disposed on one side of the electron transport layer close to the light emitting layer. In this embodiment, also on the basis of not affecting the electrical properties of the electron transport layer, by disposing the high refractive index material on one side of the electron transport layer close to the light emitting layer, on the one hand, the high refractive index material has a high refractive index, which is equivalent to adding a layer of high refractive index material layer with a high refractive index between the light emitting layer and the electron transport layer, and the high refractive index material layer can improve the light energy loss caused by the refractive index difference between the electron transport layer and the light emitting layer, and on the other hand, the high refractive index material forms a large number of scattering centers so that the light emitted by the light emitting layer is concentrated to the light emitting position at the top or bottom of the light emitting device, thereby effectively increasing the light extraction efficiency of the light emitting device and reducing the light energy loss.

[0064] In one embodiment, the molar ratio of the N-type semiconductor material to the high refractive index material is 1:0.001 to 1:0.05. In this embodiment, the N-type semiconductor material is used for electron transport, and the high refractive index material is used to improve the light energy loss of the light-emitting device. It is understandable that if the high refractive index material is added in too much amount, the electrical properties of the electron transport layer will be affected, thereby reducing the luminous efficiency of the light-emitting layer of the light-emitting device. If the high refractive index material is added in too little amount, the light extraction efficiency of the light-emitting device is not significantly improved, and it is difficult to effectively improve the technical problem of large light energy loss in the light-emitting device.

[0065] Therefore, in this embodiment, when the molar ratio of the N-type semiconductor material and the high refractive index material in the electron transport layer is 1:0.001 to 1:0.05, for example, the molar ratio of the N-type semiconductor material and the high refractive index material is 1:0.002, 1:0.003, 1:0.004, 1:0.005, 1:0.006, 1:0.007, 1:0.008, 1:0.009, 1:0.01, 1:0.02, 1:0.03, 1:0.04, etc., without affecting the electrical properties of the electron transport layer, the technical problem of large light energy loss in the light-emitting device can be effectively improved.

[0066] Wherein, the average particle size of the high refractive index material is 15-25 nm; and / or the average particle size of the N-type semiconductor material is 5-12 nm.

[0067] In this embodiment, the average particle size of the high refractive index material is greater than the average particle size of the electron transport layer, which is conducive to forming multiple scattering centers in the electron transport layer. Through the multiple scattering centers, the light emitted by the light-emitting layer is more concentratedly scattered or transmitted to the top or bottom light output position of the light-emitting device.

[0068] Specifically, in this embodiment, the high refractive index material is selected from one of a polymer compound or a first compound, wherein the polymer compound is selected from at least one of poly(pentabromophenyl methacrylate), poly(pentabromobenzyl acrylate), poly(pentabromobenzyl methacrylate), poly(2,4,6-tribromophenyl methacrylate), poly(vinyl phenyl sulfate), poly(2-vinylthiophene), and poly(2-chlorostyrene), or a block copolymer of the above polymer monomers; the first compound can be one or more of a titanium compound, a zirconium compound, a niobium compound, a tantalum compound, and a hafnium compound, wherein the titanium compound can be titanium dioxide, the zirconium compound can be zirconium oxide, the niobium compound can be niobium oxide, the tantalum compound can be tantalum oxide, and the hafnium compound can be hafnium oxide. The N-type semiconductor material is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, and the doping ratio is 0-50%; the II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.

[0069] Further, in this embodiment, the cathode and the anode are selected from doped metal oxide particle electrodes, composite electrodes of metal and metal oxide, graphene electrodes, carbon nanotube electrodes, metal electrodes or alloy electrodes, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0070] The material of the light-emitting layer is an organic light-emitting material or a quantum dot light-emitting material, and the organic light-emitting material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermal One or more of an activation delay material, a polymer containing BN covalent bonding, a hybrid localized charge transfer excited state material, and an exciplex luminescent material, wherein the quantum dot luminescent material is selected from one or more of a single structure quantum dot, a core-shell structure quantum dot, and a perovskite semiconductor material, wherein the material of the single structure quantum dot, the core material of the core-shell structure quantum dot, and the shell material of the core-shell structure quantum dot are selected from at least one of a II-VI group compound, an IV-VI group compound, a III-V group compound, and an I-III-VI group compound, respectively, wherein the II-V Group I compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSe S, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZ At least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe,The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2, the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors, and the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs, + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the organic-inorganic hybrid perovskite semiconductors, the general structural formula of which is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0071] Furthermore, in this embodiment, if Figure 2 As shown, the light-emitting device further includes a hole functional layer disposed between the anode and the light-emitting layer, and the hole functional layer includes a hole injection layer 5 and a hole transport layer 6 .

[0072] Wherein, the material of the hole transport layer is selected from 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-di(4-(N,N'-diphenyl ...N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-di(4-(N,N'-diphenyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-di(4-(N,N'-diphenyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-di(4-(N,N'-diphenyl)-1,1'-biphenyl triphenylamine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine) (poly-TPD), polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene) ), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) (PVK) and its derivatives, polymethyl methacrylate At least one of acrylates and their derivatives, poly(9,9-octylfluorene) and their derivatives, poly(spirofluorene) and their derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, and doped or undoped CuO.

[0073] Among them, the material of the hole injection layer is selected from at least one of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0074] In addition, the embodiments of the present application also provide a method for preparing a light-emitting device, such as Figure 3 As shown, the prepared light-emitting device is an upright device, and the preparation method of the light-emitting device includes:

[0075] S10, providing a substrate having an anode;

[0076] S20, forming a light-emitting layer on the anode;

[0077] S30, forming an electron transport layer on the light-emitting layer;

[0078] S40, forming a cathode on the electron transport layer;

[0079] The material of the electron transport layer includes an N-type semiconductor material and a high refractive index material, and the refractive index of the high refractive index material is greater than 1.5.

[0080] In step S10 of this embodiment, the anode is selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0081] In this embodiment, the provided substrate with an anode needs to be pretreated in order to facilitate the subsequent formation of the light-emitting layer on the anode. Specifically, the steps of pretreatment of the substrate with an anode include: cleaning the surface with a detergent to preliminarily remove stains on the surface, and then ultrasonically cleaning in deionized water, acetone, anhydrous ethanol, and deionized water for 20 minutes respectively to remove impurities on the surface, and drying with an inert gas to obtain a clean substrate with an anode.

[0082] In step S20 of this embodiment, the material of the light-emitting layer is selected from one or more of organic light-emitting materials and quantum dot light-emitting materials. For example, the material of the light-emitting layer can be CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, etc.

[0083] Specifically, the formation of the light-emitting layer on the substrate with the anode is carried out by spin coating, that is, a solution including the light-emitting layer material is provided, and then the solution including the light-emitting layer material is spin-coated into a film, and the light-emitting layer can be obtained after annealing, wherein the thickness of the prepared light-emitting layer is controlled by adjusting the concentration of the solution including the light-emitting layer material, the spin coating speed and the spin coating time. In this embodiment, the spin coating speed is 2000-3000rpm, the spin coating time is 30-60s, the annealing temperature is 120-200℃, and the annealing time is 20-40min. Preferably, the spin coating speed is 3000rpm, the spin coating time is 30s, the annealing temperature is 150℃, and the annealing time is 30min. The thickness of the prepared light-emitting layer is 20-60nm.

[0084] Further, in step S30, the step of forming an electron transport layer on the light-emitting layer includes:

[0085] S31, providing a mixed solution containing the N-type semiconductor material and the high refractive index material;

[0086] S32, forming the electron transport layer on the light-emitting layer by using the mixed solution; or

[0087] S33, providing a first solution containing the high refractive index material and a second solution containing the N-type semiconductor material;

[0088] S34, forming a first film layer on the light-emitting layer using the first solution, and then forming a second film layer on the first film layer using the second solution;

[0089] Wherein, the first film layer and the second film layer constitute the electron transport layer.

[0090] In this embodiment, the material of the electron transport layer is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, and the material of the high refractive index material is selected from one of polymer compounds or metal oxides, wherein the molar ratio of the N-type semiconductor material to the high refractive index material is 1:0.001 to 1:0.05, the average particle size of the high refractive index material is 15-25nm, and the average particle size of the N-type semiconductor material is 5-12nm.

[0091] In this embodiment, the electron transport layer prepared by step S31 and step S32 includes the N-type semiconductor material and the high refractive index material dispersed between the N-type semiconductor materials, and the high refractive index material in the electron transport layer prepared by step S33 and step S34 is arranged on one side of the electron transport layer close to the light-emitting layer.

[0092] Specifically, in this embodiment, the electron transport layer, the first film layer and the second film layer are formed by spin coating and annealing, wherein the spin coating speed is 3000-5000 rpm, the spin coating time is 30-60 s, the annealing temperature is 80-120° C., and the annealing time is 30-60 min. Preferably, the spin coating speed is 3000 rpm, the spin coating time is 30 s, the annealing time is 80° C., and the annealing time is 30 min. In this embodiment, the thickness of the prepared electron transport layer is 20-60 nm.

[0093] Furthermore, in step S40, the cathode is selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. After the cathode is manufactured, the prepared light-emitting device is packaged. The packaging process can be performed by machine packaging or manual packaging. The oxygen content and water content in the packaging environment are both lower than 0.1ppm to ensure the stability of the prepared light-emitting device.

[0094] Furthermore, in one embodiment, the light-emitting device further includes a hole functional layer, namely, a hole injection layer and a hole transport layer. Therefore, the method for preparing the light-emitting device in this embodiment further includes, before forming the light-emitting layer on the anode in step S20:

[0095] Step 50: forming a hole functional layer on the anode, wherein the hole functional layer includes a hole injection layer and a hole transport layer.

[0096] Specifically, the material of the hole injection layer and the material of the hole transport layer are respectively prepared into corresponding solutions, the prepared solution including the material of the hole injection layer is spin-coated onto the substrate having the anode, and the hole injection layer is obtained after annealing. Thereafter, the prepared solution including the material of the hole transport layer is spin-coated onto the hole injection layer, and the hole transport layer is obtained after annealing, wherein the spin coating speed is 3000-5000rpm, the spin coating time is 30-60s, the annealing temperature is 100-150°C, and the annealing time is 30-60min. Preferably, the spin coating speed is 3000rpm, the spin coating time is 30s, the annealing time is 150°C, and the annealing time is 30min. In this embodiment, the thickness of the prepared hole injection layer and the hole transport layer is 20-40nm.

[0097] In addition, the embodiments of the present application also provide another method for preparing a light-emitting device, such as Figure 4 As shown, the prepared light-emitting device is an inverted device, and the preparation method of the light-emitting device includes:

[0098] S60, providing a substrate having a cathode;

[0099] S70, forming an electron transport layer on the cathode;

[0100] S80, forming a light-emitting layer on the electron transport layer;

[0101] S90, forming an anode on the light-emitting layer;

[0102] The material of the electron transport layer includes an N-type semiconductor material and a high refractive index material, and the refractive index of the high refractive index material is greater than 1.5.

[0103] In step S60 of this embodiment, the cathode is selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0104] In this embodiment, the provided substrate with a cathode needs to be pretreated in order to facilitate the subsequent formation of the electron transport layer on the cathode. Specifically, the steps of pretreatment of the substrate with a cathode include: cleaning the surface with a detergent to preliminarily remove stains on the surface, and then ultrasonically cleaning in deionized water, acetone, anhydrous ethanol, and deionized water for 20 minutes respectively to remove impurities on the surface, and drying with an inert gas to obtain a clean substrate with a cathode.

[0105] Further, in step S70, the step of forming an electron transport layer on the substrate having a cathode includes:

[0106] S71, providing a mixed solution containing the N-type semiconductor material and the high refractive index material;

[0107] S72, forming the electron transport layer on the light-emitting layer by using the mixed solution; or

[0108] S73, providing a third solution containing the N-type semiconductor material and a fourth solution containing the high refractive index material;

[0109] S74, forming a third film layer on the light-emitting layer using the third solution, and then forming a fourth film layer on the third film layer using the fourth solution;

[0110] Wherein, the third film layer and the fourth film layer constitute the electron transport layer.

[0111] In this embodiment, the material of the electron transport layer is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, and the material of the high refractive index material is selected from one of polymer compounds or metal oxides, wherein the molar ratio of the N-type semiconductor material to the high refractive index material is 1:0.001 to 1:0.05, the average particle size of the high refractive index material is 15-25nm, and the average particle size of the N-type semiconductor material is 5-12nm.

[0112] In this embodiment, the electron transport layer prepared by step S71 and step S72 includes the N-type semiconductor material and the high refractive index material dispersed between the N-type semiconductor materials, and the high refractive index material in the electron transport layer prepared by step S73 and step S74 is arranged on one side of the electron transport layer close to the light-emitting layer.

[0113] Specifically, in this embodiment, the electron transport layer, the first film layer and the second film layer are formed by spin coating and annealing, wherein the spin coating speed is 3000-5000 rpm, the spin coating time is 30-60 s, the annealing temperature is 80-120° C., and the annealing time is 30-60 min. Preferably, the spin coating speed is 3000 rpm, the spin coating time is 30 s, the annealing time is 80° C., and the annealing time is 30 min. In this embodiment, the thickness of the prepared electron transport layer is 20-60 nm.

[0114] In step S80 of this embodiment, the material of the light-emitting layer is selected from one or more of organic light-emitting materials and quantum dot light-emitting materials. For example, the material of the light-emitting layer can be CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, etc.

[0115] Specifically, the formation of the light-emitting layer on the electron transport layer is carried out by spin coating, that is, a solution including the light-emitting layer material is provided, and then the solution including the light-emitting layer material is spin-coated into a film, and the light-emitting layer can be obtained after annealing, wherein the thickness of the prepared light-emitting layer is controlled by adjusting the concentration of the solution including the light-emitting layer material, the spin coating speed and the spin coating time. In this embodiment, the spin coating speed is 2000-3000rpm, the spin coating time is 30-60s, the annealing temperature is 120-200℃, and the annealing time is 20-40min. Preferably, the spin coating speed is 3000rpm, the spin coating time is 30s, the annealing temperature is 150℃, and the annealing time is 30min. The thickness of the prepared light-emitting layer is 20-60nm.

[0116] Furthermore, in step S90, the anode is selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. After the anode is manufactured, the prepared light-emitting device is packaged. The packaging process can be performed by machine packaging or manual packaging. The oxygen content and water content in the packaging environment are both lower than 0.1ppm to ensure the stability of the prepared light-emitting device.

[0117] Furthermore, in one embodiment, the light-emitting device further includes a hole functional layer, namely, a hole injection layer and a hole transport layer. Therefore, the method for preparing the light-emitting device in this embodiment further includes, before forming an anode on the light-emitting layer in step S90:

[0118] Step 100: forming a hole functional layer on the light-emitting layer, wherein the hole functional layer includes a hole injection layer and a hole transport layer.

[0119] Specifically, the material of the hole injection layer and the material of the hole transport layer are respectively prepared into corresponding solutions, the prepared solution including the material of the hole transport layer is spin-coated onto the light-emitting layer, and the hole transport layer is obtained after annealing. Thereafter, the prepared solution including the material of the hole injection layer is spin-coated onto the hole transport layer, and the hole injection layer is obtained after annealing, wherein the spin coating speed is 3000-5000rpm, the spin coating time is 30-60s, the annealing temperature is 100-150°C, and the annealing time is 30-60min. Preferably, the spin coating speed is 3000rpm, the spin coating time is 30s, the annealing time is 150°C, and the annealing time is 30min. In this embodiment, the thickness of the prepared hole injection layer and the hole transport layer is 20-40nm.

[0120] In addition, an embodiment of the present application further provides a display device, including the light-emitting device, or a light-emitting device prepared by the method for preparing the light-emitting device.

[0121] The following is a further explanation of a light emitting device and a method for preparing the same, and a display device of the present application through specific embodiments:

[0122] In this embodiment, taking the N-type semiconductor material as ZnO and the high refractive index material as poly(pentabromophenyl methacrylate) or zirconium oxide as an example, the preparation process of the mixed solution containing the N-type semiconductor material and the high refractive index material is first described in detail.

[0123] The preparation of the mixed solution comprises the steps of (1) synthesizing ZnO nanoparticles by a solution method and (2) adding a high refractive index material to form a mixed solution; specifically, the step (1) comprises: adding a zinc salt to an organic solvent to prepare a solution with a concentration of 0.1-1 M, and adding dropwise a 0.1-1 M alkaline ethanol solution (OH) at room temperature. - With Zn 2+ The molar ratio of ZnO to ZnO is 1.5 to 3.0:1, and the pH value is 12 to 14), and the solution is stirred for 1 to 4 hours to obtain a clear and transparent solution. Thereafter, ZnO nanoparticles are precipitated with acetone, centrifuged and vacuum dried to obtain ZnO nanoparticles; wherein the zinc salt can be zinc chloride, zinc nitrate, zinc acetate, etc., the base can be sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, etc., and the organic solvent can be dimethyl sulfoxide or dimethylformamide.

[0124] Specifically, step (2) comprises: adding poly(pentabromophenyl methacrylate) or zirconium oxide to an ethanol solution containing ZnO nanoparticles, and ultrasonically treating the solution at room temperature for 10 minutes to 4 hours to obtain the mixed solution, wherein the molar ratio of poly(pentabromophenyl methacrylate) or zirconium oxide to ZnO nanoparticles is 1:0.001-1:0.05.

[0125] In the following examples, the mixed solution used to prepare the ZnO (poly (pentabromophenyl methacrylate)) layer was prepared as follows:

[0126] (1) Zinc chloride is added to an organic solvent to prepare a solution with a concentration of 0.5 M, and a 0.6 M sodium hydroxide ethanol solution is added dropwise at room temperature and stirred for 1.5 h to obtain a clear and transparent solution. Thereafter, ZnO nanoparticles are precipitated with acetone, vacuum dried after centrifugation, and then dissolved and dispersed with ethanol to obtain a ZnO ethanol solution.

[0127] (2) adding poly(pentabromophenyl methacrylate) high refractive index material to the ZnO ethanol solution, and ultrasonically treating the solution at room temperature for 2 hours to obtain the mixed solution, wherein the molar ratio of poly(pentabromophenyl methacrylate) to ZnO nanoparticles is 1:0.01.

[0128] The average particle size of the ZnO nanoparticles is 10 nm, and the average particle size of the poly(pentabromophenyl methacrylate) nanoparticles is 25 nm.

[0129] The mixed solution for preparing the ZnO (zirconium oxide) layer is prepared as follows:

[0130] (1) Zinc chloride is added to an organic solvent to prepare a solution with a concentration of 0.5 M, and a 0.6 M sodium hydroxide ethanol solution is added dropwise at room temperature and stirred for 1.5 h to obtain a clear and transparent solution. Thereafter, ZnO nanoparticles are precipitated with acetone, vacuum dried after centrifugation, and then dissolved and dispersed with ethanol to obtain a ZnO ethanol solution.

[0131] (2) adding zirconium oxide nanoparticles to the ZnO ethanol solution and subjecting the solution to ultrasonic treatment at room temperature for 2 hours to obtain the mixed solution, wherein the molar ratio of zirconium oxide to ZnO nanoparticles is 1:0.01.

[0132] The average particle size of the ZnO nanoparticles is 10 nm, and the average particle size of the zirconium oxide nanoparticles is 25 nm.

[0133] Example 1

[0134] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO(poly(pentabromophenyl methacrylate)) / Ag, wherein the molar ratio of ZnO to poly(pentabromophenyl methacrylate) is 1:0.001, and the thickness of the ZnO (poly(pentabromophenyl methacrylate)) layer is 40 nm. It should be noted that in the present embodiment, the ZnO and poly(pentabromophenyl methacrylate) in the ZnO (poly(pentabromophenyl methacrylate)) layer are in a doped state rather than a layered state.

[0135] The preparation process of the light emitting device comprises:

[0136] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropyl alcohol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0137] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0138] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0139] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0140] Spin coating the aforementioned mixed material of ZnO and poly(pentabromophenyl methacrylate) on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0141] A 100nm thick layer of metal Ag is thermally evaporated on the electron transport plate through a mask as a cathode;

[0142] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0143] Example 2

[0144] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO(poly(pentabromophenyl methacrylate)) / Ag, wherein the molar ratio of ZnO to poly(pentabromophenyl methacrylate) is 1:0.01, and the thickness of the ZnO (poly(pentabromophenyl methacrylate)) layer is 40 nm. It should be noted that in the present embodiment, the ZnO and poly(pentabromophenyl methacrylate) in the ZnO (poly(pentabromophenyl methacrylate)) layer are in a doped state rather than a layered state.

[0145] The preparation process of the light emitting device comprises:

[0146] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropanol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0147] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0148] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0149] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0150] Spin coating the aforementioned mixed material of ZnO and poly(pentabromophenyl methacrylate) on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0151] A 100nm thick layer of metal Ag is thermally evaporated on the electron transport plate through a mask as a cathode;

[0152] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0153] Example 3

[0154] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO(poly(pentabromophenyl methacrylate)) / Ag, wherein the molar ratio of ZnO to poly(pentabromophenyl methacrylate) is 1:0.05, and the thickness of the ZnO (poly(pentabromophenyl methacrylate)) layer is 40 nm. It should be noted that in the present embodiment, the ZnO and poly(pentabromophenyl methacrylate) in the ZnO (poly(pentabromophenyl methacrylate)) layer are in a doped state rather than a layered state.

[0155] The preparation process of the light emitting device comprises:

[0156] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropanol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0157] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0158] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0159] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0160] Spin coating the aforementioned mixed material of ZnO and poly(pentabromophenyl methacrylate) on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0161] A 100nm thick layer of metal Ag is thermally evaporated on the electron transport plate through a mask as a cathode;

[0162] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0163] Example 4

[0164] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO(poly(pentabromophenyl methacrylate)) / Ag, wherein the molar ratio of ZnO to poly(pentabromophenyl methacrylate) is 1:0.1, and the thickness of the ZnO (poly(pentabromophenyl methacrylate)) layer is 40 nm. It should be noted that in the present embodiment, the ZnO and poly(pentabromophenyl methacrylate) in the ZnO (poly(pentabromophenyl methacrylate)) layer are in a doped state rather than a layered state.

[0165] The preparation process of the light emitting device comprises:

[0166] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropyl alcohol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0167] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0168] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0169] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0170] Spin coating the aforementioned mixed material of ZnO and poly(pentabromophenyl methacrylate) on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0171] A 100nm thick metal Ag layer is thermally evaporated on the electron transport plate through a mask plate as a cathode;

[0172] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0173] Example 5

[0174] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO (zirconium oxide) / Ag, wherein the molar ratio of ZnO to zirconium oxide is 1:0.001, and the thickness of the ZnO (zirconium oxide) layer is 40 nm. It should be noted that in the present embodiment, the ZnO and zirconium oxide in the ZnO (zirconium oxide) layer are in a doped state rather than a layered state.

[0175] The preparation process of the light emitting device comprises:

[0176] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropyl alcohol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0177] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0178] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0179] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0180] Spin coating the aforementioned mixed material of ZnO and zirconium oxide on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0181] A 100nm thick metal Ag layer is thermally evaporated on the electron transport plate through a mask plate as a cathode;

[0182] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0183] Example 6

[0184] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO (zirconium oxide) / Ag, wherein the molar ratio of ZnO to zirconium oxide is 1:0.01, and the thickness of the ZnO (zirconium oxide) layer is 40 nm. It should be noted that in the present embodiment, the ZnO and zirconium oxide in the ZnO (zirconium oxide) layer are in a doped state rather than a layered state.

[0185] The preparation process of the light emitting device comprises:

[0186] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropyl alcohol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0187] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0188] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0189] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0190] Spin coating the aforementioned mixed material of ZnO and zirconium oxide on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0191] A 100nm thick metal Ag layer is thermally evaporated on the electron transport plate through a mask plate as a cathode;

[0192] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0193] Example 7

[0194] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO (zirconium oxide) / Ag, wherein the molar ratio of ZnO to zirconium oxide is 1:0.05, and the thickness of the ZnO (polyzirconium oxide) layer is 40nm. It should be noted that in the present embodiment, the ZnO and zirconium oxide in the ZnO (zirconium oxide) layer are in a doped state rather than a layered state.

[0195] The preparation process of the light emitting device comprises:

[0196] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropyl alcohol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0197] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0198] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0199] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0200] Spin coating the aforementioned mixed material of ZnO and zirconium oxide on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0201] A 100nm thick metal Ag layer is thermally evaporated on the electron transport plate through a mask plate as a cathode;

[0202] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0203] Example 8

[0204] The present embodiment is a positive light-emitting device, and the structure of the light-emitting device is: ITO / PEDOT:PSS / TFB / CdS / ZnO (zirconium oxide) / Ag, wherein the molar ratio of ZnO to zirconium oxide is 1:0.1, and the thickness of the ZnO (zirconium oxide) layer is 40nm. It should be noted that in the present embodiment, the ZnO and zirconium oxide in the ZnO (zirconium oxide) layer are in a doped state rather than a layered state.

[0205] The preparation process of the light emitting device comprises:

[0206] Providing a conductive glass with an ITO anode, cleaning it with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning it in deionized water, isopropyl alcohol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen;

[0207] The anode is placed on a homogenizer, a PEDOT:PSS material is spin-coated on the anode, and annealed at 150° C. for 30 min to obtain a hole injection layer with a thickness of 40 nm;

[0208] Spin coating the TFB material on the hole injection layer, annealing at 150° C. for 30 min, to obtain a hole transport layer with a thickness of 40 nm;

[0209] Spin coating CdS quantum dot material on the hole transport layer, annealing at 80° C. for 30 min, to obtain a light-emitting layer with a thickness of 30 nm;

[0210] Spin coating the aforementioned mixed material of ZnO and zirconium oxide on the light-emitting layer, annealing at 80° C. for 30 min, to obtain an electron transport layer with a thickness of 40 nm;

[0211] A 100nm thick layer of metal Ag is thermally evaporated on the electron transport plate through a mask as a cathode;

[0212] The light emitting device is packaged in an environment where the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting device.

[0213] Comparative Example 1

[0214] This comparative example is a vertical light-emitting device, the structure of which is: ITO / PEDOT:PSS / TFB / CdS / ZnO / Ag, and the thickness of the ZnO layer is 40 nm.

[0215] Further, in this embodiment, the photoelectric properties of the light-emitting devices prepared in Examples 1-8 and the light-emitting device prepared in Comparative Example 1 were tested, and the results are shown in the following table:

[0216]

[0217] It can be seen from the data in the table that the external quantum efficiency (EQE) of the light-emitting devices prepared in Examples 1 to 8 is significantly higher than the external quantum efficiency of the light-emitting device prepared in Comparative Example 1, while the turn-on voltage is significantly lower than the turn-on voltage of the light-emitting device prepared in Comparative Example 1.

[0218] Among them, because the average particle size of the high refractive index material is 15-25nm, and the average particle size of the N-type semiconductor material is 5-12nm, the average particle size of the high refractive index material is larger than the average particle size of the N-type semiconductor material, so that the light emitted by the light-emitting layer in the light-emitting device can be more concentratedly scattered or transmitted to the light-emitting position at the top or bottom of the light-emitting device after passing through the high refractive index material, thereby increasing the light extraction efficiency and reducing the light energy loss.

[0219] At the same time, according to the test results of the external quantum efficiency of the light-emitting devices prepared according to Examples 1 to 4, and the test results of the external quantum efficiency of the light-emitting devices prepared according to Examples 5 to 8, it can be seen that when the molar ratio of the high refractive index material to the ZnO nanoparticles is 1:0.01, the test results are optimal.

[0220] Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A light-emitting device, comprising an anode and a cathode arranged opposite to each other, a light-emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the cathode and the light-emitting layer, characterized in that: The material of the electron transport layer includes an N-type semiconductor material and a high refractive index material, wherein the refractive index of the high refractive index material is greater than 1.

5.

2. The light emitting device according to claim 1, characterized in that: The material of the electron transport layer includes the N-type semiconductor material and the high refractive index material dispersed between the N-type semiconductor materials.

3. The light emitting device according to claim 1, characterized in that: The high refractive index material is arranged on a side of the electron transport layer close to the light emitting layer.

4. The light emitting device according to any one of claims 1 to 3, characterized in that: The molar ratio of the N-type semiconductor material to the high refractive index material is 1:0.001 to 1:0.

05.

5. The light emitting device according to any one of claims 1 to 3, characterized in that: The average particle size of the high refractive index material is 15-25 nm; and / or The average particle size of the N-type semiconductor material is 5-12 nm.

6. The light emitting device according to claim 1, characterized in that: The high refractive index material is selected from one of a polymer compound or a first compound, wherein the polymer compound is selected from at least one of poly(pentabromophenyl methacrylate), poly(pentabromobenzyl acrylate), poly(pentabromobenzyl methacrylate), poly(2,4,6-tribromophenyl methacrylate), poly(vinyl phenyl sulfate), poly(2-vinylthiophene), and poly(2-chlorostyrene) or a block copolymer of more than one polymer monomer; the first compound includes one or more of a titanium compound, a zirconium compound, a niobium compound, a tantalum compound, and a hafnium compound, wherein the titanium compound includes titanium dioxide, the zirconium compound includes zirconium oxide, the niobium compound includes niobium oxide, the tantalum compound includes tantalum oxide, and the hafnium compound includes hafnium oxide; and / or The N-type semiconductor material is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, and the doping ratio is 0-50%; the II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.

7. The light emitting device according to claim 1, characterized in that: The cathode and the anode are selected from doped metal oxide particle electrodes, composite electrodes of metal and metal oxide, graphene electrodes, carbon nanotube electrodes, metal electrodes or alloy electrodes. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba. And / or The material of the light-emitting layer is an organic light-emitting material or a quantum dot light-emitting material, and the organic light-emitting material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermal One or more of an activation delay material, a polymer containing BN covalent bonding, a hybrid localized charge transfer excited state material, and an exciplex luminescent material, wherein the quantum dot luminescent material is selected from one or more of a single structure quantum dot, a core-shell structure quantum dot, and a perovskite semiconductor material, wherein the material of the single structure quantum dot, the core material of the core-shell structure quantum dot, and the shell material of the core-shell structure quantum dot are selected from at least one of a II-VI group compound, an IV-VI group compound, a III-V group compound, and an I-III-VI group compound, respectively, wherein the II-V Group I compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSe S, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZ At least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe,The III-V compound is selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN P, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2, the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors, and the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs, + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the organic-inorganic hybrid perovskite semiconductors, the general structural formula of which is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

8. The light emitting device according to claim 1, characterized in that: The light emitting device further comprises a hole functional layer disposed between the anode and the light emitting layer, wherein the hole functional layer comprises a hole injection layer and a hole transport layer; The material of the hole transport layer is selected from 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)- N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly[2-methoxy- 5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, At least one of poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or The material of the hole injection layer is selected from at least one of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

9. A method for preparing a light emitting device, characterized in that: include: providing a substrate having an anode; forming a light-emitting layer on the anode; forming an electron transport layer on the light-emitting layer; forming a cathode on the electron transport layer; or providing a substrate having a cathode; forming an electron transport layer on the cathode; forming a light-emitting layer on the electron transport layer; forming an anode on the light-emitting layer; The material of the electron transport layer includes an N-type semiconductor material and a high refractive index material, and the refractive index of the high refractive index material is greater than 1.

5.

10. The method for preparing a light emitting device according to claim 9, characterized in that: The step of forming an electron transport layer on the light-emitting layer comprises: Providing a mixed solution containing the N-type semiconductor material and the high refractive index material; Forming the electron transport layer on the light-emitting layer by using the mixed solution; or Providing a first solution containing the high refractive index material and a second solution containing the N-type semiconductor material; forming a first film layer on the light-emitting layer using the first solution, and then forming a second film layer on the first film layer using the second solution; Wherein, the first film layer and the second film layer constitute the electron transport layer.

11. The method for preparing a light emitting device according to claim 9, characterized in that: The step of forming an electron transport layer on the cathode comprises: Providing a mixed solution containing the N-type semiconductor material and the high refractive index material; Forming the electron transport layer on the light-emitting layer by using the mixed solution; or Providing a third solution containing the N-type semiconductor material and a fourth solution containing the high refractive index material; forming a third film layer on the cathode by using the third solution, and then forming a fourth film layer on the fourth film layer by using the fourth solution; Wherein, the third film layer and the fourth film layer constitute the electron transport layer.

12. The method for preparing a light emitting device according to any one of claims 9 to 11, characterized in that: The molar ratio of the N-type semiconductor material to the high refractive index material in the electron transport layer is 1:0.001 to 1:0.05; and / or The average particle size of the high refractive index material is 15-25 nm; and / or The average particle size of the N-type semiconductor material is 5-12 nm.

13. The method for preparing a light emitting device according to any one of claims 9 to 11, characterized in that: The high refractive index material is selected from one of a polymer compound or a zirconium compound, wherein the polymer compound is selected from at least one of poly(pentabromophenyl methacrylate), poly(pentabromobenzyl acrylate), poly(pentabromobenzyl methacrylate), poly(2,4,6-tribromophenyl methacrylate), poly(vinyl phenyl sulfate), poly(2-vinylthiophene), and poly(2-chlorostyrene); the zirconium compound is selected from zirconium oxide; and / or The N-type semiconductor material is selected from at least one of metal oxides, doped metal oxides, II-VI semiconductor materials, III-V semiconductor materials and I-III-VI semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, the II-VI semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the III-V semiconductor material is selected from at least one of InP and GaP; the I-III-VI semiconductor material is selected from at least one of CuInS and CuGaS.

14. A display device, characterized in that: A light-emitting device comprising the light-emitting device according to any one of claims 1 to 8, or a light-emitting device prepared by the method for preparing the light-emitting device according to any one of claims 9 to 13.